Determination of structures of Ca2CoSi2O7, Ca2MgSi2O7, and Ca2(Mg0.55Fe0.45)Si2O7 in incommensurate and normal phases and observation of diffuse streaks at high temperature - Kusaka K.; Hagiya K.; Ohmasa M.; Okano Y.; Mukai M.; Iishi K.; Haga N. (My University, 2001)
The structures of Ca2CoSi2O7, Ca2MgSi2O7, and Ca2(Mg0.55Fe0.45)Si2O7 have been determined in the temperature range between 297 and 773 K with arbitrary intervals. The structures of the incommensurate phase of the three compounds are characterized by the presence of the six-, seven-, and eight-coordinated Ca–O polyhedra and of the bundles along the c-axes consisting of four arrays of the six-coordinated Ca–O polyhedra and an array of T1O4 (T1: Co, Mg, or Mg–Fe) tetrahedra in the structures. The number of bundles in each material decreases at elevated temperatures. The incommensurate phase undergoes a phase transition into the normal phase at 493 K in Ca2CoSi2O7, at 360 K in Ca2MgSi2O7, and at 510 K in Ca2(Mg0.55Fe0.45)Si2O7. The features of the structures of the normal phase are almost the same as those found in the basic structures (the averaged structures of the incommensurate structures), and this fact implies that the characteristics of the structures, such as the six-coordinated Ca–O polyhedra or fragments of the bundles, should be partially preserved at higher temperatures both in the incommensurate structures and also in the structures of the normal phase. Analyses of anisotropic displacement parameters clarified that disorder of the modulation waves is developed in the structures at higher temperatures. The evolution of a disorder in the structures was ascertained by observation of the circular diffuse streaks in the vicinity of the transition temperature between the incommensurate and normal phases.
Keywords: AKERMANITE; STRUCTURES; INCOMMENSURATE PHASE; NORMAL PHASE; DISORDER